A Review on the Economic Assessment of Integrating Macro-Encapsulated Phase Change Material in Building Envelopes - Ahmed, Amal; Elgohary, Germin; Nessim, Ashraf (Journal of engineering sciences and information technology, 2024)
The worldwide energy crisis has made energy-saving a topic of concern in almost every country. Previous research has explored the use of thermal energy storage materials (TES), such as phase change materials (PCMs), as an effective energy-saving technique. Among various immersion techniques, macro-encapsulation has proven to be efficient, safe, and convenient. However, choosing the right PCM system can be complicated due to the variety of available PCM types, encapsulation materials, and encapsulation shapes. Moreover, while macro-encapsulated PCM systems are efficient, their feasibility depends on several factors, including energy prices, economic situation, and climatic conditions. Therefore, this research aims to provide a comprehensive overview to help create a deeper understanding of the design and application of macro-encapsulated PCM systems. It explains the different types of PCM, encapsulation materials, and encapsulation shapes, guiding the selection for the most appropriate system regarding the surrounding environment. Additionally, it aims to present a guideline for conducting feasibility studies on energy-saving systems such as PCM. A total of 80 research papers covering the intersection between the thermal performance of PCM and the economic assessment have been categorized, studied, and analyzed in order to identify the most accurate method of assessing the system’s feasibility. By providing a base knowledge regarding the various types of each element of the system and the factors that govern the selection of each, this research will help engineers appropriately design the system. In addition, providing a detailed guideline to the assessment of the system shall aid the decision makers in determining the system’s feasibility which encourages its application. Finally, the research investigates and addresses the key issues for future studies.